The St. Louis African American community and the Exodusters - Jack, Bryan M., 1969- (University of Missouri Press, 2007)
"A story of former slaves searching for their own promised land after the Civil War. Fleeing the South, and trying to reach Kansas, many became stranded in St. Louis. Jack tells how the city's African American community provided food, shelter, and funds to help the Exodusters complete their journey"--Provided by publisher.